PENGARUH AKUNTABILITAS, TRANSPARANSI DAN PARTISIPASI TERHADAP PENGELOLAAN KEUANGAN DI YAYASAN SANTA FAMILIA (PANTI BHAKTI KASIH SITI ANNA) - Irma Abi, Maria; Maharani, Yunita; Shinta Lestari, Deara (Jurnal Ilmiah Niaga Bisnis Elektronik, 2022)
The foundation is a non-profit company, and financial management within the company is the main key to the company's operational activities. Foundations have an obligation to disclose information about the source and use of the funds that have been obtained so that accountability, transparency, and participation are maintained. The purpose of this study was to determine the effect of accountability, transparency, and participation on financial management at the Santa Familia Foundation (Panti Bhakti Kasih Siti Anna). The approach used in this study uses a quantitative approach with the sampling technique used is purpose sampling. Methods of data collection with 46 respondents. Data analysis used multiple regression analysis. The results of the study indicate that accountability, transparency, and participation together have a positive and significant effect on financial management. The test results are proven by the F test where F count 15,068 > from F table 2.82 and partially accountability and participation have a positive effect on financial management as evidenced by the T-test where t count 2,129 > t table 1,682 for accountability variables and t count 5,132 > t Table 1.682 for the participation variable.